2020
DOI: 10.1590/1806-3713/e20190006
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, asthma, and respiratory symptoms: a population-based study

Abstract: Objective: To estimate the prevalence of respiratory symptoms and asthma, according to body mass index (BMI), as well as to evaluate factors associated with physician-diagnosed asthma, in individuals ≥ 40 years of age. Methods: This was a population-based cross-sectional study conducted in Florianópolis, Brazil, with probability sampling. Data were collected during home visits. Demographic data were collected, as were reports of physician-diagnosed asthma, respiratory symptoms, medications in use, and comorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
15
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 33 publications
(56 reference statements)
3
15
0
5
Order By: Relevance
“…This is in line with the findings of a 2007 meta-analysis showing that obesity precedes the development of asthma, nearly doubling the odds of incident asthma. In their study, Souza et al (3) also showed that the prevalence of respiratory symptoms, particularly dyspnea and wheezing, are highest in obese individuals, irrespective of smoking status. Notably, the authors found that, among nonsmokers, chronic expectoration and chronic bronchitis-like symptoms were most common in those who were obese, whereas the prevalence of chronic expectoration did not differ by weight category among current and former smokers.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…This is in line with the findings of a 2007 meta-analysis showing that obesity precedes the development of asthma, nearly doubling the odds of incident asthma. In their study, Souza et al (3) also showed that the prevalence of respiratory symptoms, particularly dyspnea and wheezing, are highest in obese individuals, irrespective of smoking status. Notably, the authors found that, among nonsmokers, chronic expectoration and chronic bronchitis-like symptoms were most common in those who were obese, whereas the prevalence of chronic expectoration did not differ by weight category among current and former smokers.…”
mentioning
confidence: 86%
“…In conclusion, the Souza et al study (3) provides important new data regarding the association between obesity and a diagnosis of asthma, as well as the clinical consequences…”
mentioning
confidence: 86%
See 3 more Smart Citations